Foliage potted plant assessment for urban and peri-urban areas - Jain, Ritu; Vanlalruati, Vanlalruati; Tiwari, A K; Singh, Babita (Indian Horticulture, 2021)
Indoor plants have been used for over a century in commercial high rise buildings for aesthetic and psychological purposes. These plants are used both for exterior and interior decoration purpose for beautifying the surroundings. Since, city dwellers spend 90% of their time indoors and indoor air quality is a major health issue. Therefore, use of foliage potted plants in the indoors can help in combating indoor air pollution, improving the health status and increasing the productivity of the human resources. Therefore, foliage plants namely Red edge Dracaena, Areca palm, Goodluck Plant and Araucaria are suitable ornamentals for outdoor conditions, while Song of India, Xanadu, Money Plant, Arrowhead plant, Cardboard palm, Crotons are suitable for indoors conditions. However, Chinese fan palm was found suitable for both indoor and outdoor conditions. Therefore, the city dwellers can still manage to breathe in fresh air and keep polluted air at bay by growing these ornamental plants in and around their surroundings.